Effect of Qualitative Exercises by Assistance Tools to Develop the Ability to Timing with Complex Skill (Blocking, Rolling, Receiving the Ball and Lay- Up) for Basketball Players Under 16 Years - Wameedh Ali Hassoon Almali; Aied Hussain Abdul Ameer; Hayder mohammed Abd-Alhadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of research lies in the preparation of qualitative exercises, which researchers studies theaffect in the development of the ability complex skills of basketball people. The aim of this study: is tohave a positive effect in the ability to timing the situation and the performance of the complex skills withthe basketball (blocking and rolling, receiving the ball and lay- up ) The researchers used the experimentalmethod divided in two groups to solving the research problem, and the research community has been knownas the basketball players under 16 years of the National Center for the Care of Sports of Babylon for thesports season 2020-2021 ,(12) players, and were divided in two equal groups. The most important conclusionswere: The period of the experiment by using suggested exercises, was suitable in the development of theability to timing the situation and the complex skills in the basketball of the experimental research group.The most important recommendations were: The researchers recommend focus on the qualitative exercisesas basic in training under16 years players in basketball, and the need to use modern tools of assistance intraining because there effective in learning and the best performance of complex skills in basketball .